2018
DOI: 10.1080/07036337.2018.1513499
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating implementation of EU fiscal governance

Abstract: Since 1997 the Economic and Monetary Union has been centred on the Stability and Growth Pact (SGP), which provides the framework for the coordination of economic policies and the surveillance of fiscal policies of member states. The country-specific recommendations, which address the member states' macroeconomic programmes, are the policy instruments of the SGP preventive arm. At the same time, these recommendations are the object of intense negotiation between the Commission and the Council. Why are these rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Applying this argument, powerful states are more likely to water down the Commission's recommendations because of the influence they exert in the Council. 2 Therefore, and following the same logic as in Baerg and Hallerberg (2016) and Mariotto (2019), we expect that larger countries with greater voting weights are more successful in weakening the Commission's recommendations. A third hypothesis we test as follows.…”
Section: Causal Mechanismsmentioning
confidence: 74%
See 3 more Smart Citations
“…Applying this argument, powerful states are more likely to water down the Commission's recommendations because of the influence they exert in the Council. 2 Therefore, and following the same logic as in Baerg and Hallerberg (2016) and Mariotto (2019), we expect that larger countries with greater voting weights are more successful in weakening the Commission's recommendations. A third hypothesis we test as follows.…”
Section: Causal Mechanismsmentioning
confidence: 74%
“…Do edits to the drafts of the Commission's texts merely represent the fixing of minor errors and fine‐tuning, or do they contain evidence of substantively more interesting dynamics such as domestic political pressures and power politics? Previous research found that, in the lead‐up to the GFC, the Council weakened evaluations the European Commission had originally prepared for member states with more eurosceptic populations as well as the evaluations for politically influential states (for example Baerg and Hallerberg, 2016; Mariotto, 2019). Given the reforms made under the European Semester, the question is whether these two factors predict when the Council weakens the Commission's evaluations of member state economic programmes in the post‐reform era.…”
Section: Theory and Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars used content analysis (Di Mascio et al, 2020;Mariotto, 2019;Raudla, 2010;Raudla et al, 2020), discourse analysis (Warren, 2018(Warren, , 2020Warren et al, 2017), and process tracing method (Degner & Leuffen, 2020). The quantitative approach was used in three studies, with descriptive statistics in Malová and Dolný (2016) and inferential statistics in Kaplan (2017) and Nicoli (2019).…”
Section: Factors In the Choice Of The Fiscal Governance Frameworkmentioning
confidence: 99%